Association between radiographic features of knee osteoarthritis and pain: results from two cohort studies. (21st August 2009) - Neogi, Tuhina; Felson, David; Niu, Jingbo; Nevitt, Michael; Lewis, Cora E; Aliabadi, Piran; Sack, Burt; Torner, James; Bradley, Lawrence; Zhang, Yuqing
Abstract : Objective To examine the relation of radiographic features of osteoarthritis to knee pain in people with knees discordant for knee pain in two cohorts. Design Within person, knee matched, case-control study. Setting and participants Participants in the Multicenter Osteoarthritis (MOST) and Framingham Osteoarthritis studies who had knee radiographs and assessments of knee pain. Main outcome measures Association of each pain measure (frequency, consistency, and severity) with radiographic osteoarthritis, as assessed by Kellgren and Lawrence grade (0-4) and osteophyte and joint space narrowing grades (0-3) among matched sets of two knees within individual participants whose knees were discordant for pain status. Results 696 people from MOST and 336 people from Framingham were included. Kellgren and Lawrence grades were strongly associated with frequent knee pain—for example, for Kellgren and Lawrence grade 4 v grade 0 the odds ratio for pain was 151 (95% confidence interval 43 to 526) in MOST and 73 (16 to 331) in Framingham (both P<0.001 for trend). Similar results were also seen for the relation of Kellgren and Lawrence scores to consistency and severity of knee pain. Joint space narrowing was more strongly associated with each pain measure than were osteophytes. Conclusions Using a method that minimises between person confounding, this study found that radiographic osteoarthritis and individual radiographic features of osteoarthritis were strongly associated with knee pain.